Biomaterials in Endodontics: a review - Ponnada, Naveena; Praveen, Dalavai; Sajjan, Girija S; Manohar, P N V; Sindhuja, B V; Varma, K Meghana (International Journal of Dental Materials, 2023)
Biomaterials have evolved over the past three decades and are relatively specialized, highly biocompatible, but low-strength dental materials. Bioactive materials can interact with living tissues or systems. The newly emerging bioactive category of dental materials has expanded clinical uses in restorative dentistry and endodontics. Examples of bioactive materials are  Calcium Silicate containing Mineral Trioxide Aggregate (Portland cement); Calcium Silicate cements lacking aluminium and containing phosphate: Bioagrregate,  iRoot SP and iRoot BP (Endosequence), Calcium Silicate cements containing predominantly Tricalcium Silicate: Bio-active Glass, Calcium Phosphate based materials: Tricalcium Phosphate, Hydroxyapatite, Calcium Phosphate cements and Calcium Aluminate based materials: GIC based luting cements; Bioactive Glass. Other biomimetic materials include Emdogain, Platelet Rich Plasma, Platelet Rich Fibrin, Bone grafts and barrier membranes. Thus, the objective of this review was to compare and review the composition, and properties of these bioactive materials in endodontics.